RECОGNITIОN OF THE BIОLОGICАL АSSETS АCCОRDING TO THE IАS-41- АGRICULTURE IN UZBEKISTАN - Ikrоmjоn ugli, Аdkhаmоv Sаmаriddin (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: Supporting the measurement based on the fair value invokes a series of reasons that conclude that the fair value, as a method of measurement of the future economic benefits that is expected to be generated by the biological assets, has a greater relevance, reliability, comparability and intelligibility that the historic cost, and it is for this reason that we find more biological assets on active markets with clear market prices. Method: The measurement of the biological assets cost is sometimes less reliable than the measurement of the fair value, because the coupled products and the coupled costs can generate situations where the relationship between inputs and outputs is incorrectly defined, leading to complex and arbitrary cost allocations even if the biological assets generate supplementary biological assets, and the latter are used for the agriculture activity characteristic to the entity. The International Accounting Standard IAS 41 – Agriculture prescribes accounting treatment, financial sheet drawing and information related to biological assets and agricultural activities from the harvesting point. This standard does not treat the processing of produce obtained after harvesting, because this process is described by IAS 2 – Stoks. International accounting standard – IAS 41 – Agriculture does not contain specific information related to how often one should evaluate biological assets, deducing that the evaluation must be conducted on each closing date, because there are no existent regulations to stipulate a less frequent evaluation of biological assets. Results: The presence of such prices increases significantly the reliability of the market value, as indicator of the fair value. This standard presents the general idea that the fair value can be realistically estimated by using deductive hierarchy, which this article will debate, for a better understanding of initial evaluation and consecutive evaluation of biological assets. IAS 41 is treating the management of biological assets: increasing the agricultural output, logging, plant cultivation; horticulture and aquaculture. The biological alteration is the process of growing, ageing, production and procreation of biological assets; these alteration lead to new agricultural produce, or transformation of other biological assets. In addition, IAS 41 does not contain any specific information referring how often one should estimate the biological assets. We can conclude that that the estimation must be conducted on each closure, because the standard does not state any information on how frequent the estimation must be run. Novelty: As explanation, IASB stated the availability of fair values on relative expected costs, and the consistent progress of biological transformations. In the case of biological assets or agricultural produce that are similar, IAS 41 allows grouping them in order to simplify the fair value estimation. The relevant characteristics for grouping the assets are: nature, naturalness, consumption possibility, and quality and production capacity.